2015
DOI: 10.1159/000381289
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Isolation of <b><i>Aspergillus</i></b> and <b><i>Candida </i></b>from Sputum in Patients with Non-Cystic Fibrosis Bronchiectasis

Abstract: Background: Information on the role of fungi in non-cystic fibrosis (CF) bronchiectasis is lacking. Objectives: Our aim was to determine the prevalence of and factors associated with the isolation and persistence of fungi from sputum in these patients. Methods: We performed a multicenter observational study comprising adult patients with non-CF bronchiectasis. Persistence of Aspergillus spp. and Candida albicans was defined as the presence of ≥2 positive sputum cultures taken at least 6 months apart within a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 37 publications
0
56
0
Order By: Relevance
“…Haemophilus influenzae and P. aeruginosa are the most commonly isolated organisms in several European studies using aerobic selective cultures, although no organisms are isolated in 23-27% of patients [9,17,36,37]. New methods to study lung microbiota have found that the diversity of airway infection is underestimated, with anaerobic bacteria found in up to 83% of sputum samples, and that three taxa, Streptococcaceae, Pseudomonadaceae and Pasturellaceae, seem to be dominant [38]. However, most microbiome studies in bronchiectasis to date have been small, and therefore the clinical importance of this information is uncertain.…”
Section: Consensus Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Haemophilus influenzae and P. aeruginosa are the most commonly isolated organisms in several European studies using aerobic selective cultures, although no organisms are isolated in 23-27% of patients [9,17,36,37]. New methods to study lung microbiota have found that the diversity of airway infection is underestimated, with anaerobic bacteria found in up to 83% of sputum samples, and that three taxa, Streptococcaceae, Pseudomonadaceae and Pasturellaceae, seem to be dominant [38]. However, most microbiome studies in bronchiectasis to date have been small, and therefore the clinical importance of this information is uncertain.…”
Section: Consensus Statementmentioning
confidence: 99%
“…However, most microbiome studies in bronchiectasis to date have been small, and therefore the clinical importance of this information is uncertain. Few data have been published regarding the prevalence of fungal colonisation and it is now possible to perform sequencing of the fungal "mycobiome" in a similar way to that described above for bacteria [38][39][40]. The prevalence of nontuberculous mycobacteria (NTM) in Europe is <10%, although there seems to be a broad geographic variation [41].…”
Section: Consensus Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory viral9 and fungal10 infections have also been linked to bronchiectasis disease markers, which suggests that multiple infectious agents can contribute to the pathophysiology of non-cystic fibrosis bronchiectasis. While genetic loci in genes related to inflammation and airway remodelling have been previously investigated in non-cystic fibrosis bronchiectasis,11–15 little is known regarding common genetic polymorphisms that affect microbial acquisition in patients.…”
Section: Introductionmentioning
confidence: 99%
“…are the fungi that are most usually isolated in the respiratory tract of patients with respiratory chronic diseases, such as bronchiectasis [31, 32]. Some authors have suggested that nebulised antibiotics could be a predisposing risk factor for fungal respiratory infections [11, 12].…”
Section: Discussionmentioning
confidence: 99%